2017
DOI: 10.1017/s0007114516004499
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the effects of iodine prophylaxis in the adult population of southern Italy with deficient and sufficient iodine intake levels: a cross-sectional, epidemiological study

Abstract: I prophylaxis is the most effective strategy to eradicate I deficiency disorders, but it has been shown to affect the thyroid disease pattern. In this study, we assessed the frequency of thyroid disorders in an adult population living in two areas of southern Italy after implementing I prophylaxis. To this aim, a cross-sectional, population-based study including 489 subjects from an I-deficient rural and an I-sufficient urban area of southern Italy was conducted. Thyroid ultrasound was performed on all partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Indeed, Olivieri et al [5] reported that iodized salt accounted for 55% of salt sales in Italy in 2012. Moreover, in recent surveys in northeastern Italy, 70-80% of families declared that they used iodized salt daily [9,11], while in a study conducted in Calabria the percentage of families using iodized salt was 64-82% in rural-urban areas [23]. Of the 136 subjects attending our Center for Secondary Hypertension, 62% declared using iodized salt, since, at the beginning of the study, all these patients had had a consultation with a dietitian and had received written nutritional advice [16].…”
Section: Discussionmentioning
confidence: 98%
“…Indeed, Olivieri et al [5] reported that iodized salt accounted for 55% of salt sales in Italy in 2012. Moreover, in recent surveys in northeastern Italy, 70-80% of families declared that they used iodized salt daily [9,11], while in a study conducted in Calabria the percentage of families using iodized salt was 64-82% in rural-urban areas [23]. Of the 136 subjects attending our Center for Secondary Hypertension, 62% declared using iodized salt, since, at the beginning of the study, all these patients had had a consultation with a dietitian and had received written nutritional advice [16].…”
Section: Discussionmentioning
confidence: 98%
“…Despite the clear benefits of iodine prophylaxis, continuous surveillance of adverse effects induced by iodine intake needs to be carefully maintained. Thus, the frequency of thyroid disorders along with the levels of antithyroid antibodies (TgAb and TPOAb) in 560 adult subjects from Laino and from the urban area of Cosenza were evaluated [36]. As expected, the prevalence of subjects affected by goiter was significantly higher in the rural area than in the urban area, but interestingly it was significantly lower compared with that reported in the adult population living in the same rural area in 2007 (42.6% rural area in 2007 vs. 13.8% rural area in 2015, p < 0.0001).…”
Section: Status Of Iodine Intake Over the Last Two Decades In The mentioning
confidence: 99%
“…The activities of the OERC also include an assessment of the iodine content in salt on the market. Salt samples, taken from the subjects screened (131 subjects from the rural area and 235 subjects from the urban area) during our epidemiological surveys, were found to be compliant with the iodine content permitted by Italian law (30 mg/kg) [36]. The data on sale trends of iodized salt in Calabria, supplied by the Italian Salt Company, one of the most important sales producers/distributors in the region, showed an increasing trend over the last few decades, reaching a coverage rate of approximately 65% [36].…”
Section: Status Of Iodine Intake Over the Last Two Decades In The mentioning
confidence: 99%
See 1 more Smart Citation